Perceived organizational justice and turnover intention among hospital healthcare workers - Mengstie, Missaye Mulatie (BMC Psychol, 2020)
BACKGROUND: Organizational justice is the first virtue in social institutions (J Manage 16:399-432, 1990). It is one of the most determinant factors for an effective utilization of human resources and an essential predictor of organizational success (J Manag Dev 28:457-477, 2009). Employees who perceive fairness are more likely happy with their job and less likely leave their organization (Int J Bus Manage 4:145-154, 2009). Perceived injustice, on the other hand, diminishes motivation of workers to accomplish their duties (Int J Bus Manage 4:145-154, 2009; J Educ Sci Univ Tabriz 2:27-34, 2009). Ethiopia has given emphasis to the expansion of health institutions and increasing the number of health professionals. Despite this, little emphasis has been given the human resource aspect of the health sector. Therefore, this study aims to investigate organizational justice perceptions and turnover intentions among healthcare workers in Amhara region. METHODS: One hundred ninety seven healthcare workers participated in the study. Data were collected through self- report questionnaire and semi-structured interview. The quantitative data were analyzed through MANOVA, multiple regression, and independent samples t-test. The qualitative data were analyzed through thematic analysis. RESULTS: The results of this study revealed that healthcare workers in the public hospitals held low perceived distributive, procedural, interpersonal and informational justice. Similarly, private hospitals healthcare workers had low perceptions on distributive and procedural justice. On the contrary, healthcare workers in private hospitals reported high perception of fairness on interpersonal and informational justice aspects. Both public and private hospital healthcare workers had high turnover intention. The result revealed significant difference in organizational justice perceptions between private and public hospital healthcare workers (F (4, 182) = 9.17; p < .05; partial η2 =. 168). Organizational justice dimensions (distributive, procedural, interpersonal and informational justice) significantly contributed an additional 9.9% variation in turnover intention (R (2) change = .099, F (4,170) = 4.86, p < .05). Distributive justice was the most important predictor of turnover intention (β = −.23, p < .05). CONCLUSION: Organizational justice perceptions of healthcare workers significantly predicted turnover intention. Hence, organizational justice should be given due emphasis in designing and implementing policies and strategies of human resource management.